Care programme approach – time to move beyond?. (24th September 2018) - Kingdon, David
Abstract : The Care Programme Approach (CPA) has been instrumental in embedding principles of holistic collaborative assessment and management into mental health care. Initially, its implementation was assisted by targeting those at greatest need. However dichotomising patients into more and less severe is now considered unhelpful and has been demonstrated to be unreliable. Division of patients into severe and not severe categories is no more logical than such a division of patients with physical health problems. CPA principles are now applied to all patients in mental health services and practice needs to move to individualised care, focusing on meeting quality standards and achieving positive outcomes. A system based on evidence-based clinical pathways and reliable measures of severity and need should replace the current approach. Declaration of interest: None.